Гіпоглікемічні стани у дітей і підлітків - Большова, О. В. (Clinical Endocrinology and Endocrine Surgery, 2011)
The present review describes in detail the possible causes of hypoglycemic states in childhood and adolescence.. Hypoglycemic states are considered at various congenital pathology, as well as those developing as a complication of intensified insulin therapy in children with diabetes mellitus type 1. The article emphasizes the importance of the use of insulin analogues in the prevention of hypoglycemia.